A Brief Overview of Bioinspired Robust Hydrogel Based Shape Morphing Functional Structure for Biomedical Soft Robotics - Goyal, Rohit; Mitra, Santanu (Frontiers in Materials, 2022)
Inspired by many biological organisms, biomimetic and soft robotics research has been focusing on composites of soft components being reinforced by structured stiff components. In artificial soft materials, hydrogels are very similar to the biological soft tissues/organs due to, their elastic performance, “wet and soft” properties, biodegradability and biocompatibility. However, the application of hydrogel applications is often limited by their weak mechanical properties. Despite recent great progress in developing tough and flexible hydrogels, it is still challenging to achieve the optimal magnitude of toughness, modulus and stretchability all together in synthetic hydrogels. In this review we describes tough, stiff yet highly stretchable hydrogel composites via micro/nanoscale hybrid physical and chemical cross-linking and macroscale fiber reinforcement. The nature-inspired, reinforced composite soft stimuli responsive shape morphing functional structure giving them a cartilage-like behavior. They have potential applications in diverse areas, including stretchable and bio-integrated electronics, microfluidics, tissue engineering, soft robotics and biomedical devices.